Hubungan Pengetahuan Dokter Gigi Terhadap Penerapan Protokol Kesehatan di Klinik Dokter Gigi Kota Padang - Adriyeni adriyeni; Daffa Athaala Naufal (Jurnal Sehat Mandiri, 2022)
Health protocols have an important role in breaking the chain of transmission of Covid-19. The implementation of the health protocol is an action that dentists can take while treating patients to prevent the transmission of Covid-19. The purpose of this study was to determine the relationship between dentist knowledge and the application of health protocols at the Dentist Clinic in Padang City. The scope of this research is dental and oral health. The research was conducted in May - June 2022. The type of research is quantitative. The affordable population in this study were dentists in the city of Padang as many as 83 samples with simple random sampling technique. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using chi-square test, data processing using computerized SPSS program version IBM 25.0. The results of this study are that the most gender is female, namely 62 people (74.7%), the most knowledge is bad, namely 45 people (54.2%), the most actions are good, namely 43 people (51.8%), there is a relationship between knowledge of dentists with the application of health protocols at the Dentist Clinic in Padang City (p = 0.010), Conclusion: There is a relationship between dentist knowledge and the application of health protocols at the Dentist Clinic in Padang City. prevention of exposure to COVID-19 so that protection for dentists and patients is more perfect.